Anomalous glucose-responsive rheological changes in a boronic acid-modified hyaluronan. Issue 34 (11th April 2023) - Miki, Ryotaro; Yamaki, Tsutomu; Uchida, Masaki; Natsume, Hideshi
Abstract : Herein, we report anomalous glucose (Glc)-responsive gelation/solation in 3-aminophenylboronic acid-modified hyaluronic acid. Abstract : Herein, we report anomalous glucose (Glc)-responsive gelation/solation in 3-aminophenylboronic acid-modified hyaluronic acid. With 5–20 mM Glc, gelation occurred, resulting in the formation of crosslinks via Glc, which could reversibly bind to the two boronic acid sites. Solation was induced at Glc concentrations of >80 mM.